Efektifitas Penerapan Hybrid Learning dalam Meningkatkan Prestasi Belajar Pendidikan Agama Islam (PAI) dan Budi Pekerti Peserta Didik Kelas VI SDN Sidotopo I/ 48 Surabaya Pada Era New Nornal - Taufiq, Moh. Taufiq (JOIES (Journal of Islamic Education Studies), 2022)
Abstract: Covid-19 pandemic caused significant changes. Suddenly, all levels of education were forced to adapt conduct distance learning (PJJ) from home or online. This is certainly not an easy cases, because they are not fully ready and actively contributed. During the COVID-19 pandemic, especially in the new normal era, Hybrid learning is an ideal solution to various problems that occur in education fields. SDN Sidotopo I/48 as one of the schools that implements this learning model is the main attraction for researchers to conduct  especially its application in improving the learning achievement of Islamic religious education (PAI) and the character of class VI students. Therefore, the application is expected to be able to facilitate educators in achieving the objectives of the material presented, especially in the subjects of Islamic Religious Education/PAI and Characters. The method used in this research is a qualitative research method with an ethnographic and phenomenological approach. Thus the results of the research found in this study stated that the Hybrid learning implementation of Islamic Religious Education /PAI and Budi Pekerti/Characters Class VI SDN Sidotopo I/48 Surabaya in the New Normal Era in improving learning achievement was quite effective, this can be seen from the observations results and list of values ​​held by Islamic Religious Education /PAI teachers and Budi Pekerti/Character during the learning process in pandemic to new normal era.